Optimizing Mathematics Instruction in Accordance with Vision and Mission in a Favorite School through Lesson Study - Shahnaz Nurazizah; Suparni Suparni; Tantyo Margono (Journal of Instructional Mathematics, 2024)
This study employs a qualitative descriptive approach to optimize mathematics instruction at SMA Negeri 8 Yogyakarta through lesson study, aligning with the school's vision of fostering Higher Order Thinking Skills (HOTS) and critical thinking. Conducted in Class X E7 during the 2024/2025 academic year, the research was implemented over two cycles, encompassing planning, implementation, and reflection phases. An expository teaching model combined with the drill method was utilized to enhance conceptual understanding and problem-solving skills. Findings indicate that lesson study facilitated structured instructional refinements, improving student engagement and mathematical proficiency. Summative assessment results showed that 60% of students met the mastery criteria, reflecting progress in instructional effectiveness. However, challenges remained, particularly in students' ability to interpret HOTS-based contextual problems and manage time effectively during problem-solving tasks. Adjustments in cycle II, including extended time allocation and structured sequencing of exercises, led to improved problem-solving accuracy but did not fully address all learning gaps. This study highlights the effectiveness of lesson study in integrating HOTS and fostering critical thinking in mathematics instruction. Future recommendations include strengthening conceptual foundations, diversifying contextual HOTS-based problems, and incorporating time management strategies to optimize instructional outcomes.